The Relationship, Scientific Evidence, and Clinical Implications Between Obesity and Psoriasis: A Literature Review - Eka Lustikawati; Dwi Sarwani Sri Rejeki; Siwi Pramatama (Faculty of Medicine, Universitas Tadulako, 2026)
Background: Obesity and psoriasis are chronic diseases often found together. Obesity not only increases the risk of developing psoriasis but also worsens its clinical severity. Objective: This study aims to systematically review the association between obesity and psoriasis and examine their clinical implications. Methods: A systematic literature review was conducted following PRISMA guidelines. Literature searches were performed using Google Scholar, PubMed, and ScienceDirect. From 19,150 articles identified, 10 studies were selected based on inclusion and exclusion criteria. Results: The findings show a positive correlation between higher body mass index (BMI) and increased severity of psoriasis, measured by PASI (Psoriasis Area and Severity Index), BSA (Body Surface Area), and DLQI (Dermatology Life Quality Index). This relationship is mediated by the role of adipokines, pro-inflammatory cytokines, and the activation of the Th17 immune pathway. Genetic predisposition and unhealthy lifestyles further contribute to the association. Conclusion: Obesity is an important factor that worsens psoriasis severity. Comprehensive clinical management should integrate weight control and lifestyle interventions to improve treatment outcomes for patients with psoriasis.